Exploring Causal Relationships between Circulating Inflammatory Proteins and Thromboangiitis Obliterans: A Mendelian Randomization Study - Zhang, Bihui; He, Rui; Yao, Ziping; Li, Pengyu; Niu, Guochen; Yan, Ziguang; Zou, Yinghua; Tong, Xiaoqiang; Yang, Min (Thrombosis and Haemostasis, 2024)
Background Thromboangiitis obliterans (TAO) is a vascular condition characterized by poor prognosis and an unclear etiology. This study employs Mendelian randomization (MR) to investigate the causal impact of circulating inflammatory proteins on TAO.Methods In this MR analysis, summary statistics from a genome-wide association study meta-analysis of 91 inflammation-related proteins were integrated with independently sourced TAO data from the FinnGen consortium's R10 release. Methods such as inverse variance weighting, MR–Egger regression, weighted median approaches, MR-PRESSO, and multivariable MR (MVMR) analysis were utilized.Results The analysis indicated an association between higher levels of C–C motif chemokine 4 and a reduced risk of TAO, with an odds ratio (OR) of 0.44 (95% confidence interval [CI]: 0.29–0.67; p = 1.4 × 10−4; adjusted p = 0.013). Similarly, glial cell line-derived neurotrophic factor exhibited a suggestively protective effect against TAO (OR: 0.43, 95% CI: 0.22–0.81; p = 0.010; adjusted p = 0.218). Conversely, higher levels of C–C motif chemokine 23 were suggestively linked to an increased risk of TAO (OR: 1.88, 95% CI: 1.21–2.93; p = 0.005; adjusted p = 0.218). The sensitivity analysis and MVMR revealed no evidence of heterogeneity or pleiotropy.Conclusion This study identifies C–C motif chemokine 4 and glial cell line-derived neurotrophic factor as potential protective biomarkers for TAO, whereas C–C motif chemokine 23 emerges as a suggestive risk marker. These findings elucidate potential causal relationships and highlight the significance of these proteins in the pathogenesis and prospective therapeutic strategies for TAO.
Keywords: thromboangiitis obliterans; Mendelian randomization; inflammatory proteins; biomarkers; therapeutic target